Establishing evidence-based training of cognitive behavioural therapy treatments: empirical and theoretical guidance for dissemination - Rakovshik, S (2011)
The need to provide effective Cognitive Behavioural Therapy (CBT) treatments in routine clinical practice necessitates effective methods of CBT training, which are scalable and can be disseminated in populations without ready access to specialist trainers or large scale funding. This thesis seeks to add theoretical and empirical guidance to the development of evidence-based CBT training. The first chapter reviews the current literature on effective CBT training, and suggests theoretical and methodological guidance for future research on evidence-based training practices. Cohort studies (Chapters 2 – 4) examine data from former trainees for guidance on accurate CBT competence measurement and effective CBT training components. The fifth and sixth chapters report randomised-controlled trials examining the effects of internet-based training (IBT) on therapists’ competence and patient outcomes (Chapter 6). Findings from the literature review (Chapter 1) and Chapter 2 suggested the need for training effectiveness trials using treatment trial methodology, which includes ‘blind’ observer ratings of therapist behaviour as the measure of competence. Chapter 3 found that extensive training led to significant improvement in competence for trainees with a range of individual baseline characteristics. Since such extensive training is not accessible to the majority of practicing therapists, Chapter 4 examined which elements of extensive training were perceived by trainees as having the greatest positive effect on competence; thus providing empirical guidance in planning more scalable forms of training, such as IBT. Findings from the first four chapters provided guidance in planning the two randomised controlled trials outlined in Chapters 5 and 6, resulting in rigorous empirical data showing significant positive effects of IBT on therapists’ competence and on their patients’ clinical outcomes. Finally, the results of this thesis are related to the framework for developing evidence-based training, which was suggested in Chapter 1 and suggestions for future research are made.